2020
DOI: 10.3928/23258160-20200228-07
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Morphologic Findings at Four Years After Intravitreal Bevacizumab or Laser for Type 1 ROP

Abstract: BACKGROUND AND OBJECTIVE: To compare morphologic and functional status at age 4 years for patients treated in one eye with laser photocoagulation and the other eye with intravitreal bevacizumab (IVB) injection for Type 1 retinopathy of prematurity (ROP). PATIENTS AND METHODS: In this single-center, randomized, controlled trial, best-corrected visual acuity (BCVA) in logMAR was obtained along with spherical equivalent refraction (SER), fluorescein angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It suggested that immature development of inner retinal layers and delayed development of the ellipsoid zone at the foveal center might have been induced by laser photocoagulation in ROP patients. Lepore et al have compared 36 eyes of 18 patients with one eye treated with laser photocoagulation and the other eye treated with intravitreal bevacizumab injection for type 1 ROP 24 . Eyes treated with intravitreal bevacizumab tended to have thinner foveal thickness than eyes treated with laser photocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…It suggested that immature development of inner retinal layers and delayed development of the ellipsoid zone at the foveal center might have been induced by laser photocoagulation in ROP patients. Lepore et al have compared 36 eyes of 18 patients with one eye treated with laser photocoagulation and the other eye treated with intravitreal bevacizumab injection for type 1 ROP 24 . Eyes treated with intravitreal bevacizumab tended to have thinner foveal thickness than eyes treated with laser photocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in posterior zone-affected severe ROP patients, this treatment results in low efficacy and high ocular complications. 9 13 14 15 In recent years, anti-VEGF agents are considered an attractive therapeutic strategy because of their key role in the pathophysiology of disease and advantages over ablative therapy, especially in Zone 1. 16 …”
Section: Discussionmentioning
confidence: 99%
“…The persistent avascular retina can stimulate reactivation or recurrence of the vasoproliferation, as evidenced in studies of preterm infant eyes treated with bevacizumab for severe ROP. 7 …”
Section: Introductionmentioning
confidence: 99%